Islamic Education and Islamic Revivalism in Indonesia : A Case Study of Kuttab Al-Fatih Purwokerto - Aji Sofanudin; Ahwan Fanani; Rahmawati Prihastuty (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Kuttab is a new phenomenon in the Indonesian education system. Apart from pesantren, madrasa, and Islamic schools which are publicly familiar and formally recognized by the Indonesian government, kuttab new actor and joins the Islamic education arena with the specific offer on Quranic and Islamic belief learning. This study aims at revealing ideological roots of Kuttab Al-Fatih (KAF) and analyzing its educational concept. Kuttab Al-Fatih is selected because of its rapid spread and success to establish 34 branches throughout Indonesia. Using a qualitative approach to study KAFs in Purwokerto, the study shows that KAF embraces conservative and fundamentalistic thought in Islam. The educational concept of kuttab is idealizing past glorious Islamic institutions and civilization. Therefore, the spirit of KAF is to restore ideal Islamic education of the past.